Triticum aestivum L. ve Triticum compactum türlerine ait buğdayların DSC metodu ile ayırtedilmesinin sağlanması - Koç, Zeynep Uca (Gebze Yüksek Teknoloji Enstitüsü, Lisansüstü Eğitim Enstitüsü, 2009)
Zeleny sedimentasyon, miksograph vb. metodlarla gluten kalitesi, miktarı ve ticari kalitesi belirlenen Tr. Aestivum türüne ait yüksek protein oranına sahip, Kozak cinsi, kırmızı sert buğday ve buğday unu, Tr. Compactum türüne ait gluten oranı düşük, beyaz, yumuşak Topbaş buğdayı ve buğday unu, saf buğday nişastası ve ticari gluten DSC cihazında termal özellikleri açısından incelendi.Buğday tanelerinde 60 oC de denatürasyon pikleri elde edildi. Pik alanları mukayese edildiğinde protein oranı yüksek olan Tr. Aestivum türüne ait ekmeklik buğdayda daha büyük pik alanı görüldü. Tr. Aestivum türüne ait buğday taneşerinin piklerinin alanı büyük olmadığından deney tekrarlarının hepsinde pikler net görülmemiştir. Piklerin netleştirilmesi için yeni çalışmalar yapılmalıdır. Piklerin netleştirilmesi ile DSC cihazı ekmeklik buğday tanelerini bisküvilik buğday tanelerinden ayırt etmede kullanılabilir.

The thermal properties of the two different flour and grain samples belonging to the Tr. Aestivum and Tr. Compactum species had been examined through using DSC device. Quantity and quality of the Gluten (Glutenin + Gliadin), which is the major storage protein of the wheat, have an important role on the technological properties and on the final product quality.The protein ratio belonging to the Tr. Aestivum species, whose glutenin quality and quantity determined as moderate by the Zeleny sedimentation, mixograph etc. methods, and the glutenin ratio obtained from red hard wheat and belonging to the Tr. Compactum species was determined as low and the flours and grains obtained from white and soft Topbas wheats had been examined for their thermal properties on the DSC device.At 60 oC, obtained denaturation peak endoterms. As the comparation with the peak areas of the Tr. Aestivum and Tr. Compactum wheat grains, larger peak area was obtained in Tr. Aestivum wheat DSC diagrams. The use of modulated DSC to characterize the glass transition of wheat grains did not allow to identify the glass transition of the main wheat components (proteins and starch). Although wheat grains or wheat flour is a mixture of polymers.
Achieving the Distinguishment of grains obtained from species of the Triticum aestivum L. and Triticum compactum by DSC
Keywords: Kimya Mühendisliği; Chemical Engineering